PENGARUH JUMLAH RESEP HARIAN TERHADAP PEMAKAIAN OBAT ESENSIAL DI PUSKESMAS PUTRI AYU KOTA JAMBI - delly wahyuni; Erna Elfrida; Samsinar (LPPM Universitas Awal Bros, 2026)
The availability and utilization of essential medicines are important indicators of pharmaceutical service quality in primary health centers. The increase in patient visits leads to a higher number of daily prescriptions which may affect essential medicine utilization. This study aimed to analyze the effect of daily prescription quantity on essential medicine utilization at Putri Ayu Primary Health Center, Jambi City. This research used a quantitative observational analytic design. Secondary data were obtained from daily prescription reports and essential medicine utilization reports from January–November 2025. Total sampling technique was applied. Data were analyzed using normality test, linearity test, heteroscedasticity test, simple linear regression, t-test, and coefficient of determination at a significance level of 0.05. The results showed that daily prescription quantity had a significant effect on essential medicine utilization (p < 0.05). The coefficient of determination indicated that variation in essential medicine utilization could be explained by daily prescription quantity. The most frequently used essential medicines were Paracetamol, Amoxicillin, and Ibuprofen. It is concluded that daily prescription quantity significantly influences essential medicine utilization; therefore, medicine planning should consider prescription trends to prevent stock shortages or overstock.